Modernity and tradition in a global era: the reinvention of caste in India - Pick, David; Dayaram, Kandy (Emerald, 2006)
Purpose - this paper aims to explore the re-interpretation and justification of caste in India in the face of modernising influences and the efforts of legislators to disassemble its structures and traditions.Approach - the concepts of de-traditionalisation and governmentality are deployed to illuminate the reconstruction of caste within the framework and imperatives of global industrial capitalism.Findings - caste now has a different source of justification in that it serves the functions and needs of the 'winners' of globalisation at the expense of the 'losers'. In traditional caste-based society each caste moved in separate social spheres. This is simply not possible in a modern capitalist state based on a web of social, economic, and political inter-dependencies. This has the potential to cause social dislocation, threatening India's economic and social well-being and development. This paper demonstrates that whilst caste is still prevalent in Indian society it can no longer appeal to tradition for legitimacy.Implications resource distribution and the creation of an inclusive environment is a critical policy issue. The challenge for social policy in India is tackling the entrenched inequality of the caste system in its emerging, contemporary form. Equal opportunities will remain imaginary, unless India takes adequate steps towards capacity building in disadvantaged social groups.Original value de-traditionalisation and governmentality have so far only been applied to developed or Western nations. This paper uses these concepts to provide a critical account of an important social issue in developing nations.